Decadal Trends in the Migration Phenology of Diadromous Fishes Native to the Burrishoole Catchment, Ireland - de Eyto, Elvira; Kelly, Seán; Rogan, Ger; French, Andrew; Cooney, Joe; Murphy, Michael; Nixon, Pat; Hughes, Pat; Sweeney, David; McGinnity, Phil; Dillane, Mary; Poole, Russell (Frontiers in Ecology and Evolution, 2022)
Migration is an important ecological trait that allows animals to exploit resources in different habitats, obtaining extra energy for growth and reproduction. The phenology (or timing) of migration is a highly heritable trait, but is also controlled by environmental factors. Numerous studies have reported the advancement of species life-events with climate change, but the rate and significance of such advancement is likely to be species specific, spatially variable and dependent on interactions with population and ecosystem changes. This is particularly true for diadromous fishes which are sentinels of change in both freshwater and marine domains, and are subject to considerable multiple stressors including overfishing and habitat degradation. Here, we describe trends in the migration phenology of three native Irish migratory fishes over half a century, Atlantic salmon (Salmo salar), brown trout (Salmo trutta) and European eel (Anguilla anguilla). The trends were derived from daily counts of 745,263 fish moving upstream and downstream through the fish traps of the Burrishoole catchment, an internationally important monitoring infrastructure allowing a full census of migrating fish. We found that the start of the seaward migration of eel has advanced by one month since 1970. The commencement of the salmon smolt migration has advanced by one week, although the rest of the migration, and the entirety of the trout smolt run has remained stable. The beginning of the upstream migration of trout to freshwater has advanced by 20 days, while the end of the run is more than one month later than in the 1970s. The greatest phenological shift has been in the upstream migration of adult salmon, with at least half of migrating fish returning between one and two months earlier from the marine environment compared to the 1970s. The earlier return of these salmon is coincident with reduced marine survival and decreasing body size, indicating considerable oceanic challenges for this species. Our results demonstrate that the impacts of climate change on the phenology of diadromous fish are context-dependent and may interact with other factors. The mobilisation of long-term datasets are crucial to parse the ecological impacts of climate change from other anthropogenic stresses.